Northern Hemisphere Extratropical Cyclone Clustering in ERA5 Reanalysis and the CESM2 Large Ensemble - Karwat, Alexia; Franzke, Christian L. E.; Pinto, Joaquim G.; Lee, Sun-Seon; Blender, Richard (Journal of Climate, 2024)
Extratropical cyclones are a dominant feature of the midlatitudes, and often occur as storm sequences. This phenomenon is known as cyclone clustering, which is common over regions like the eastern North Atlantic and western Europe. Here, intense clustered cyclones may lead to large cumulative socioeconomic impacts. There are several different approaches to quantify cyclone clustering, but a detailed evaluation on how clustering may change in a warmer climate is missing. We perform a cyclone clustering analysis for the Northern Hemisphere midlatitudes using the ERA5 reanalysis to characterize clustering during 1980–2020. Moreover, we use large ensemble simulations of the Community Earth System Model version 2 following the SSP3-7.0 scenario to compare clustering during 2060–2100 to 1980–2020. Our model simulations show significant enhancement in cyclone clustering over Europe for 3 and 4 cyclones within 7 days in the future decades, which is increasing by up to 25% on average during 2060–2100 compared to 1980–2020. In contrast, cyclone clustering decreases along the west coast of the United States and Canada by up to 24.3% and by 10.1% in the Gulf of Alaska for the same periods. In a warmer climate, clustered cyclones have lower minimum pressure and larger radii and depths compared to nonclustered events. Our findings suggest that change in future cyclone clustering depends on regions affected by global warming, with implications for the cumulative windstorm risk.